Are My Dry Cows Heat-Stressed? A Novel Approach to Assess Heat Stress of Dry Cows in Commercial Dairy Herds - A. L. Scanavez; C. A. Gamarra; R. S. de Oliveira; L. G. Mendonça (Kansas Agricultural Experiment Station Research Reports, 2019)
Heat stress during the dry period causes major economic losses to the dairy industry. However, limited research exists regarding responses of dry cows exposed to various temperature and relative humidity gradients. In addition, no validated methods are currently available to assess heat stress in dry cows. The goals of this study were to describe core body temperature (CBT) responses of dry cows according to a variety of temperature-humidity index (THI) values, and develop and validate a practical method to assess heat stress in dry cows in commercial dairy herds. This study was comprised of 2 parts. In the first part of the study, vaginal temperature of dry cows (n = 346) with 250 to 260 days of gestation from 5 herds was assessed for 4 to 7 consecutive days in 5-minute intervals. Within dairy and parity group, cows were classified as having high (HT) or low CBT (LT). By design, CBT was greater for HT compared with LT cows (102.3 ± 0.01 vs. 101.8 ± 0.01°F). Cows classified as having HT had shorter gestation length compared with their LT counterparts (272.5 ± 0.2 vs. 275.1 ± 0.2 days). The second part of the study consisted of evaluating and validating a practical assessment method of heat stress and investigating CBT threshold values. Vaginal temperature of 1,540 dry cows with 236 to 250 days of gestation from 3 commercial dairy herds was assessed a single time using a digital thermometer. Average CBT of HT cows at each THI (data from the first part of the study) was used as a threshold value to classify cows as heat-susceptible or heat-tolerant. Cows with higher or lower CBT than the threshold defined for a given THI were classified as heat-susceptible or tolerant, respectively. Cows classified as heat-susceptible had shorter gestation length (272.5 ± 0.2 vs. 275.0 ± 0.2 days) and were more likely to have twins (11.0 vs. 3.8%) than heat-tolerant cows. In conclusion, assessment of heat stress in dry cows based on defined CBT thresholds is a useful method to identify cows expected to have shorter gestation length and more likely to have twins.
Keywords: summer; dry cows; assessments method; gestational length